Lithuanian version of Child Behavior Checklist (CBCL 4/18): Some psychometric properties - Žukauskienė, Rita; Ignatavičienė, Kristina (Psichologija, 2001)
Achenbach's Child Behavior Checklist (CBCL 4/18) is accepted worldwide for assessment of children competencies and behaviour problems. As with any similar instrument, it is liable to cultural influences, hence requires reliability verification and standardisation of the instrument in particular culture where the instrument is used. This study reports on internal consistency and test-re-test reliability of the CBCL 4/18 in Lithuania, in a school-based sample (n = 2036). The analysis showed that internal consistency of anxiety/depression, withdrawal aggression, delinquency, attention, social and somatic problems scales is sufficient; however, the reliability of thought problems scale is insufficient. Limitations of current study and further steps in standardisation are discussed.
Keywords: CBCL 4/18